Pengaruh Media Uno Card dalam Model Pembelajaran Kooperatif Tipe STAD terhadap Hasil Belajar Peserta Didik Kelas XI MIPA SMA Negeri 1 Polewali Mandar (Studi pada Materi Pokok Hidrokarbon) - Husnul Sapriani; Taty Sulastry; Ramdani Ramdani (ChemEdu, 2022)
This study is a quasi-experimental research (quasi-experimental), which is aims to determine the effect of Uno card media in the cooperative learning model type STAD toward the student’s achievement of class XI MIPA SMA Negeri 1 Polewali Mandar. The study design used is " pretest posttest-only control group design". These study population were all the students of class XI MIPA SMA Negeri 1 Polewali Mandar which is consists of five classes. The sampling technique used is simple random sampling so that the sample are a class XI MIPA 5 as an experimental class and class XI MIPA 3 as control class with the number of students each 26 peoples. The independent variable in this study is the Uno card media in cooperative learning model STAD and the dependent variable is the student’s achievement. Achievement’s data were analyzed using descriptive statistics and inferential statistics. The analysis showed the average value of student’s achievement on the experimental class at pretest and posttest respectively, are 45.38 and 92.04 with an average of N-Gain 0.860 and the control classes, namely 25.50 and 82.00 with an average of N-Gain 0.774.The results of the hypothesis testing using the Mann-Whitney test values obtained Zhitung = 2.059 and the significance level of α = 0.05 was obtained Ztabel = 1.64. Therefore, Zhitung>Ztabel, so H1 is accepted and H0 is rejected. It shows that there are effect of Uno card media in the cooperative learning model type STAD toward student’s achievement of class XI MIPA SMA Negeri 1 Polewali Mandar on the subject matter of hydrocarbons.